National profile of pediatric emergency medical service utilisation in Saudi Arabia: epidemiological insights for public health and paramedic preparedness - Alghamdi, Abdulrhman; Alharbi, Rayan Jafnan; Alshibani, Abdullah; Alharbi, Meshal; Alotaibi, Ahmed M.; Alraqebah, Suliman Ali; Alqarzaee, Hisham; Alhafdi, Talal; Almubrad, Turki; Alabdali, Abdullah (Frontiers in Pediatrics, 2026)
BackgroundEmergency Medical Services (EMS) play a vital role in pediatric care by providing timely interventions that can influence outcomes. However, there is limited national evidence from Saudi Arabia describing the profile and patterns of pediatric EMS use. Understanding these patterns is essential to guide paramedic preparedness, system planning, and public health strategies. This study aimed describe the nature of characteristics of emergency calls responded by emergency medical services in Saudi Arabia for pediatric patients aged <18 years during the year of 2022.MethodsA retrospective, descriptive study was conducted using data from the Saudi Red Crescent Authority (SRCA) for the year 2022. All pediatric cases (<18 years) attended by SRCA were included. Demographic, clinical, temporal, and geographic variables were analysed using descriptive and comparative statistics.ResultsA total of 58,554 pediatric EMS cases were included. Adolescents (47.1%) and children aged 4–12 years (38.9%) formed the largest groups, with a predominance of males (66.2%) and Saudi nationals (81.7%). Most calls were received between 9:00 pm and 1:00 am, with higher frequencies observed during weekends. Regional distribution showed the highest proportions in the Western (37.2%) and Central (30.7%) regions. Among the chief complaint, the most frequent complaints were trauma (21.8%), musculoskeletal (13.3%), bleeding (10.5%), and neurological (10.1%). Most EMS activations were initiated through the 997-call line (79.0%), followed by 911 (11.1%) and mobile applications (9.9%). The majority were managed by basic life support crews (75.1%), while advanced life support attended 22.5% of cases. The median dispatch-to-scene arrival time was 11.71 min, and the median on-scene time was 12.35 min.ConclusionThis national study provides the first comprehensive profile of pediatric EMS use in Saudi Arabia. The findings highlight the predominance of adolescents and males, the significant burden of medical emergencies alongside trauma, and the broad spectrum of pediatric conditions requiring EMS response. These results emphasise the need to strengthen pediatric-focused training, optimise EMS system planning, and integrate EMS data into public health strategies to improve child health and safety in the Kingdom.